Punching strength of RC slabs with asymmetric point loads (Acta Scientiarum. Technology, 2016)
This paper presents results of tests on 18 one-way reinforced concrete slabs under point loads having as main variable the transverse flexural reinforcement ratio, the loading position and the width of the slab. The response of the slabs is described and discussed in terms of deflections, strains of the concrete and of rebars, cracking pattern, failure modes and failure loads. Experimental results are also used to discuss and evaluate theoretical treatments presented by American Concrete Institute 318 (ACI, 2014) and Eurocode 2 (Comité Européen de Normalisation [CEN], 2005). All slabs failed by punching shear and results indicate that the recommendations presented by the codes are conservative, especially those related to the prediction of one-way shear resistance of reinforced concrete flat slabs.Â